Reflexiones sobre la superioridad moral: una cartilla digital sobre el fenómeno de la limpieza social (2023)
This degree work presents a theoretical and reflective approach to moral superiority through the phenomenon of social cleansing, in order to carry out a pedagogical exercise through the elaboration of didactic material that aims at peace dialogue in the classroom. For this degree work, the main thing is eleventh grade youth, who are prone to repeat or be victims of violent behavior or moral superiority and therefore it is essential to develop this digital primer as a tool that contributes to education in an environment of harmony, tolerance and conciliation.